2018
DOI: 10.1029/2017ms001237
|View full text |Cite
|
Sign up to set email alerts
|

Matrix‐Based Sensitivity Assessment of Soil Organic Carbon Storage: A Case Study from the ORCHIDEE‐MICT Model

Abstract: Modeling of global soil organic carbon (SOC) is accompanied by large uncertainties. The heavy computational requirement limits our flexibility in disentangling uncertainty sources especially in high latitudes. We build a structured sensitivity analyzing framework through reorganizing the Organizing Carbon and Hydrology in Dynamic Ecosystems (ORCHIDEE)‐aMeliorated Interactions between Carbon and Temperature (MICT) model with vertically discretized SOC into one matrix equation, which brings flexibility in compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…It is also uncertain how sensitive SOC is to these processes. For example, the study of Huang et al (2018), who implemented a matrix-based approach to assess the sensitivity of SOC, showed that equilibrium SOC stocks are more sensitive to input than to mixing for soils in the temperate and high-latitude regions.…”
Section: Soil Carbon Dynamicsmentioning
confidence: 99%
“…It is also uncertain how sensitive SOC is to these processes. For example, the study of Huang et al (2018), who implemented a matrix-based approach to assess the sensitivity of SOC, showed that equilibrium SOC stocks are more sensitive to input than to mixing for soils in the temperate and high-latitude regions.…”
Section: Soil Carbon Dynamicsmentioning
confidence: 99%
“…In a previous model evaluation (Guimberteau et al., 2018), it was showed that ORCHIDEE‐MICT could capture the mean value and average vertical profile of soil organic carbon density in high‐latitude regions. Another study by Huang et al using a matrix‐based representation of ORCHIDEE‐MICT soil organic carbon also evaluated systematically the sensitive parameters among 34 parameters that control soil organic carbon profiles and found critical sensitivities to the active layer thickness and the cryoturbation rate (Huang et al., 2018). Here, to further improve the robustness of soil carbon turnover processes, we recommend that future versions should consider the radiocarbon data, which provide an independent constrain for the total soil carbon turnover (He et al., 2016; Lawrence et al., 2019; Mathieu, Hatté, Balesdent, & Parent, 2015; Trumbore, Sierra, & Hicks Pries, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The elevated computational efficiency by SASU enables parameter sensitivity analysis (Huang, Zhu, et al, 2018) and pool‐based data assimilation (Hararuk et al, 2015; Hararuk & Luo, 2014; Shi et al, 2018). Sensitivity of the carbon storage from 34 parameters have been evaluated (Huang, Zhu, et al, 2018). The active layer depth among 34 parameters has been identified to play important role in predicting high‐latitude soil organic carbon.…”
Section: Discussionmentioning
confidence: 99%
“…The matrix approach was initially implemented in the Terrestrial ECOsystem model (TECO) for data assimilation studies (Luo et al, 2003;Xu et al, 2006). The matrix approach has recently been applied to global land models, such as the Community Atmosphere-Biosphere-Land Exchange model (CABLE) (Xia et al, 2012(Xia et al, , 2013, LPJ-GUESS (Ahlstrom et al, 2015), ORCHIDEE (Huang, Zhu, et al, 2018), CLM3.5 (Hararuk et al, 2015;Hararuk & Luo, 2014;Rafique et al, 2016), CLM4 (Rafique et al, 2017), CLM4.5 (Huang, Lu, et al, 2018), and CLM5 in this study. The CABLE matrix model was used to accelerate its spin-up (Xia et al, 2012) and for traceability analysis to trace sources of uncertainty in model simulations of terrestrial carbon storage (Xia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%